An International Collaborative Consensus Statement on En Bloc Resection of Bladder Tumour Incorporating Two Systematic Reviews, a Two-round Delphi Survey, and a Consensus Meeting - Teoh, Jeremy Yuen-Chun; MacLennan, Steven; Chan, Vinson Wai-Shun; Miki, Jun; Lee, Hsiang-Ying; Chiong, Edmund; Lee, Lui-Shiong; Wei, Yong; Yuan, Yuhong; Yu, Chun-Pong; Chow, Wing-Kie; Poon, Darren Ming-Chun; et al. (European urology, 2020)
BACKGROUND: There has been increasing interest in en bloc resection of bladder tumour (ERBT) as an oncologically noninferior alternative to transurethral resection of bladder tumour (TURBT) with fewer complications and better histology specimens. However, there is a lack of robust randomised controlled trial (RCT) data for making recommendations. OBJECTIVE: We aimed to develop a consensus statement to standardise various aspects of ERBT for clinical practice and to guide future research. DESIGN, SETTING, AND PARTICIPANTS: We developed the consensus statement on ERBT using a modified Delphi method. First, two systematic reviews were performed to investigate the clinical effectiveness of ERBT versus TURBT (effectiveness review) and to identify areas of uncertainty in ERBT (uncertainties review). Next, 200 health care professionals (urologists, oncologists, and pathologists) with experience in ERBT were invited to complete a two-round Delphi survey. Finally, a 16-member consensus panel meeting was held to review, discuss, and re-vote on the statements as appropriate. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Meta-analyses were performed for RCT data in the effectiveness review. Consensus statements were developed from the uncertainties review. Consensus was defined as follows: (1) ≥70% scoring a statement 7-9 and ≤15% scoring the statement 1-3 (consensus agree), or (2) ≥70% scoring a statement 1-3 and ≤15% scoring the statement 7-9 (consensus disagree). RESULTS AND LIMITATIONS: A total of 10 RCTs were identified upon systematic review. ERBT had a shorter irrigation time (mean difference -7.24 h, 95% confidence interval [CI] -9.29 to -5.20, I2 = 85%, p < 0.001) and a lower rate of bladder perforation (risk ratio 0.30, 95% CI 0.11-0.83, I2 = 1%, p = 0.02) than TURBT, both with moderate certainty of evidence. There were no significant differences in recurrences at 0-12, 13-24, or 25-36 mo (all very low certainty of evidence). A total of 103 statements were developed, of which 99 reached a consensus. A summary of statements is as follows: ERBT should always be considered for treating non-muscle-invasive bladder cancer; ERBT should be considered feasible even for bladder tumours larger than 3 cm; number and location of bladder tumours are not major limitations in performing ERBT; the planned circumferential margin should be at least 5 mm from any visible bladder tumour; after ERBT, additional biopsy of the tumour edge or tumour base should not be performed routinely; for the ERBT specimen, T1 substage, and circumferential and deep resection margins must be assessed; it is safe to give a single dose of immediate intravesical chemotherapy, perform second-look transurethral resection, and give intravesical bacillus Calmette-Guérin (BCG) therapy after ERBT; and in studies of ERBT, both per-patient and -tumour analysis should be performed for different outcomes as appropriate. Important outcomes for future ERBT studies were also identified. A limitation is that as consensus statements are brief, concise and binary in nature, areas of uncertainty that are complex in nature may not be addressed adequately. CONCLUSIONS: We have provided the most comprehensive review of the evidence base to date using a meta-analysis where appropriate and applying the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology, and mobilised the international urology community to develop a consensus statement on ERBT using transparent and robust methods. The consensus statement will provide interim guidance for health care professionals who practice ERBT and inform researchers regarding ERBT-related studies in the future. PATIENT SUMMARY: En bloc resection of bladder tumour (ERBT) is a surgical technique aiming to resect a bladder tumour in one piece. We included an international panel of experts to agree on the best practice of ERBT, and this will provide guidance to clinicians and researchers in the future.
Keywords: En bloc resection of bladder tumour; nádory močového měchýře; Cystectomy; Urothelial carcinoma; cystektomie; Delphi Technique; lidé; Practice Guidelines as Topic; delfská metoda; Urinary Bladder Neoplasms; Bladder cancer; Transurethral resection of bladder tumour; Humans; směrnice pro lékařskou praxi jako téma